Periodic buckling of soft 3D printed bioinspired tubes. (July 2019) - Liu, Jiayu; Liu, Wangqu; Pantula, Aishwarya; Wang, Zheliang; Gracias, David H.; Nguyen, Thao D.
Abstract: Buckled surfaces induced by mismatched swelling and elastic properties of materials are commonly observed in nature, such as on cacti and euphorbias. The rational design and mimicry of such buckling surfaces could lead to the development of smart, adaptive, and stimuli responsive devices. We designed a 3D printed tubular structure, composed of soft swellable poly N-isopropylacrylamide (pNIPAM) segments and stiff non-swellable polyacrylamide (pAAM) segments. Similar to the shape change of Saguaro stems after rainfall, the tubes show tunable periodic buckling modes in water at the room temperature. The buckling behavior was harnessed through the development of compressive stresses in the soft swellable segments induced by the constraint of the stiff non-swellable segments. We developed a finite element model to explore the design space of this periodic buckling behavior for the tube, and used a chemo-mechanically coupled constitutive model to describe the swellable hydrogel. Inspired by the classic bar buckling problem, we constructed a phase diagram and discovered a universal design parameter that combines the effects of geometric and material properties to guide the design of periodic buckling tubes for bioinspired functional gel structures.